Modelling and analysis of wind loading effects for heliostat mirrors using computational fluid dynamics - Ahmad, Naseer; Badar, Hafiz Waqas; Ali, Hafiz Umar; Waqas, Muhammad; Mughal, Khurram Hameed (Center of Biomass & Renewable Energy (CBIORE), 2025)
This study examines the impact of wind forces on the structural integrity of heliostat assemblies in concentrated solar power systems, specifically tailored to local climatic conditions. The objective is to assess how varying elevation angles influence aerodynamic parameters, thereby informing design optimizations for enhanced operational efficiency. A computational fluid dynamics approach, utilizing the standard k-ε turbulence model, second-order implicit time formulation, and the Green-Gauss cell-based method, was employed to simulate wind interactions with a heliostat model at elevation angles of 0°, 30°, 60°, and 90°. The simulation process encompassed model development, mesh refinement, boundary condition setup, and numerical solution techniques. Post-processing analysis focused on aerodynamic characteristics such as drag and lift forces, static and dynamic pressures, turbulent kinetic energy, and turbulence intensity. Results indicate that drag force increases with elevation angle, peaking at 90°, while lift force is maximized at 30°. Additionally, static and dynamic pressures, skin friction coefficients, and turbulence parameters exhibit strong dependence on the heliostat's elevation angle. The minimum values of the skin friction coefficient, drag coefficient, and turbulence intensity were found to be 0.0111, 0.3580, and 11.42%, respectively, at an elevation angle of 0°. Moreover, the finite element analysis of the heliostat structure to evaluate its resistance under wind loading demonstrated structural integrity with acceptable stress and displacement levels. These findings provide valuable insights for engineers and researchers aiming to optimize heliostat structural dimensions, thereby enhancing the economic and operational performance of concentrated solar power systems.